2007
DOI: 10.5507/bp.2007.048
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the blood flow velocity in the pericallosal artery of children with hydrocephalus by transcranial doppler ultrasonography - preliminary results

Abstract: Aim:The goal of this study was to evaluate selected parameters of the Doppler curve of the pericallosal artery at children with hydrocephalus.Methods: 12 patients with hydrocephalus were divided into two groups. Group 1 comprised children needing cerebrospinal fl uid drainage, and group 2 comprised children without any indication for drainage or with an already inserted well-functioning drainage system. Dilatation of the cerebral ventricles was determined by transcranial ultrasonography. Following parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…After drainage procedure, RI-ACA values dropped down to the normal range because of increased values of Ved. Change of Doppler parameters before and after drainage procedure confirmed positive effect of the drainage procedure to cerebral circulation in children with hydrocephalus [319,320,387]. 3.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…After drainage procedure, RI-ACA values dropped down to the normal range because of increased values of Ved. Change of Doppler parameters before and after drainage procedure confirmed positive effect of the drainage procedure to cerebral circulation in children with hydrocephalus [319,320,387]. 3.…”
Section: Discussionmentioning
confidence: 66%
“…The results of studies showed that increased cerebrovascular resistance before drainage procedure was determined by increased intracranial pressure, which is reversible after drainage procedure. Positive impact of drainage procedure on Doppler parameters of the cerebral arteries is based on postsurgical change of cerebrovascular resistance and regulation of cerebral circulation due to decrease of intracranial pressure [319,320,384,[387][388][389][390].…”
Section: The Presence Of Bilateral Asymmetric Ventriculomegaly Characmentioning
confidence: 99%
“…It is not clear whether the initial concussion increases the risk for cerebral swelling after the second injury. It has been suggested that SIS and malignant cerebral oedema after one MTBI could be manifestations of the same pathology (13,17,18,19). In the only systematic review of this topic, a total of 17 cases of reported SIS were identifi ed in the world literature.…”
Section: Second-impact Syndromementioning
confidence: 99%
“…month and 18 years, and these studies occurred in settings outside the pediatric intensive care unit (PICU) [1][2][3][4][5][6][7]. Thus, the main issue with either technique is that there are few data in the PICU population, and the clinical meaning of transcranial Doppler findings in this population remains unclear.…”
mentioning
confidence: 99%